Incidence, diagnosis and pathophysiology of amniotic fluid embolism. (October 2014) - Ito, F.; Akasaka, J.; Koike, N.; Uekuri, C.; Shigemitsu, A.; Kobayashi, H.
Abstract Amniotic fluid embolism (AFE) is a rare clinical entity, sometimes fatal. A review was conducted to describe the frequency, diagnosis and pathophysiology of AFE. The reported incidences ranged from 1.9 cases per 100, 000 maternities (UK) to 6.1 per 100, 000 maternities (Australia), which can vary considerably, depending on the period, region of study and the definition. Although the development of amniotic fluid-specific markers would have an impact on early diagnosis, definition of AFE based on these markers is not widely accepted. To date, immunological mechanisms, amniotic fluid-dependent anaphylactic reaction and complement activation, have been proposed as potential pathogenetic and pathophysiological mechanisms. Immune cell activation induced through complement activation may be associated with the mechanism that immediately initiates maternal death, only in susceptible individuals. This review will focus on advances in the field of AFE biology and discuss the prevalence, diagnosis and pathophysiology of AFE.